2008
DOI: 10.1021/ja711192e
|View full text |Cite
|
Sign up to set email alerts
|

Split DNA Enzyme for Visual Single Nucleotide Polymorphism Typing

Abstract: Single nucleotide polymorphisms (SNPs) are the most abundant forms of genetic variations in the human genome. Large-scale sequence analysis is needed for a population-based genetic risk assessment and diagnostic tests once a mutation has been identified. However, most of the methods for SNP screening require enzymatic manipulations such as endonuclease digestion, ligation or primer extension, and often separation of the resultant products. 1 These labor intensive and time-consuming procedures are some of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(147 citation statements)
references
References 19 publications
1
144
0
1
Order By: Relevance
“…As illustrated below, several non-enzymatic techniques provide advantages of improved repeatability, decreased cost and robustness. Based on the chemical nature of the utilized probe, these techniques can be divided into three groups: methods applying nano-and magnetic-particles , (1) aptamer-and protein-based assays [47][48][49][50][51][52], (2) and other techniques utilizing bright chemically modified nucleic acid analogues [53][54][55][56][57][58][59][60]…”
Section: Toward Enzyme-free Detection Of Snpmentioning
confidence: 99%
“…As illustrated below, several non-enzymatic techniques provide advantages of improved repeatability, decreased cost and robustness. Based on the chemical nature of the utilized probe, these techniques can be divided into three groups: methods applying nano-and magnetic-particles , (1) aptamer-and protein-based assays [47][48][49][50][51][52], (2) and other techniques utilizing bright chemically modified nucleic acid analogues [53][54][55][56][57][58][59][60]…”
Section: Toward Enzyme-free Detection Of Snpmentioning
confidence: 99%
“…Zhang and Winfree have shown that single-nucleotide mutations, insertions, and deletions in the catalyst strand can result in 10-to 300-fold reductions in its efficiency in catalyzing strand exchange [17]. These reductions in signal observed with single-nucleotide mismatches are comparable to other well-developed DNA sensors [26][27][28][31][32][33]. Consistent with these findings, we observed that when a single nucleotide was changed in the toehold region (Figure 3, inset), the mutant Trigger did not yield any peroxidase activity above background even at 150 nM concentration ( Figure 3, sample #10~12).…”
Section: Resultsmentioning
confidence: 87%
“…We also demonstrate that an entropy-driven catalytic DNA circuit can function as a generic signal amplification module that allows lower concentrations of input molecules to control the production of higher concentrations of deoxyribozymes, and thus exceed the limit of stoichiometric allosteric control. The system is qualitatively sensitive to mismatches in the input nucleic acid, suggesting that the combined entropy-driven strand exchange and allosteric deoxyribozyme circuit might facilitate the future development of enzyme-free, point-of-care diagnostic assay system [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…In the detection system, the initial tool for SNP analysis is the molecular-beacon probe (19); however, the requirement for the instrument and the individually fluorescence-labeled probe is definitely costly. The peroxidase DNAzyme was selected due to its robustness, its sensitivity, and its relatively low cost (3,12,14,25,26,27,32). Here, we apply the 3:1 split DNAzyme to detect target DNA.…”
Section: Discussionmentioning
confidence: 99%